ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI ULANG MELALUI KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA IKAN BAKAR BANG JAMIL DI SITUBONDO - Badreya, Ricka Lailatul; Hamdun, Edy Kusnadi; Praja, Yudha (Fakultas Ekonomi dan Bisnis, 2023)
The aim of the study was to determine the Analysis of the Factors Affecting Repurchase Interest Through Consumer Satisfaction as an Intervening Variable in Bang Jamil Grilled Fish in Situbondo. The sampling technique used in this study was purposive sampling of 96 consumers. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that product diversity has a positive and significant effect on consumer satisfaction, consumer trust has a positive and significant effect on consumer satisfaction, product diversity has a positive and significant effect on repurchase intention, trust has a negative effect but not significant on repurchase intention, consumer satisfaction has a positive and significant effect on repurchase intention, product diversity has a positive and significant effect on repurchase intention through consumer satisfaction, consumer trust has a positive and significant effect on repurchase intention through consumer satisfaction